To question of «relanimirization» - V. P. Beloglazov; L. V. Mostovenko (Омский научный вестник)
The purpose of the publication is to identify the trapping features in an inertia-vacuum ash collector. The inertia-vacuum ash collector (IVAC) is an inertial type ash collecting device having a purification degree of gases over 95 %. The relevance of the article is confirmed by the state program of energy development, which is interested in the modernization of ash collecting devices in connection with the lowering of the maximum allowable concentration limit for ash emitted by power plants into the air. The tasks considered in the article include the description of the process of relaminirization, the presentation of its occurrence, the calculation of the corresponding values to confirm its presence during the ash removal process in the IVAC. The results are companion calculations, which are accompanied by conclusions.